Effective depolymerization of concentrated acid hydrolysis lignin using a carbon-supported ruthenium catalyst in ethanol/formic acid media - Kristianto, Ivan; Limarta, Susan Olivia; Lee, Hyunjoo; Ha, Jeong-Myeong; Suh, Dong Jin; Jae, Jungho (ELSEVIER SCI LTD, 2017)
Lignin isolated by two-step concentrated acid hydrolysis of empty fruit bunch (EFB) was effectively depolymerized into a high-quality bio-oil using formic acid (FA) as an in-situ hydrogen source and Ru/C as a catalyst in supercritical ethanol. A bio-oil yield of 66.3 wt% with an average molecular weight of 822 g/mol and an aromatic monomer content of 6.1 wt% was achieved at 350 degrees C and a FA-to-lignin mass ratio of 3 after a reaction time of 60 min. The combination of Ru/C and FA also resulted in a significant reduction in the oxygen content of the bio-oil by similar to 60% and a corresponding increase in the higher heating value (HHV) to 32.7 MJ/kg due to the enhanced hydrodeoxygenation activity. An examination of the FA decomposition characteristics revealed that Ru/C provides a greater increase in the rate of hydrogen production from FA, explaining the efficient depolymerization of lignin in a combined system. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: KRAFT LIGNIN; TRANSFER HYDROGENATION; FORMIC-ACID; CHEMICALS; FUELS; HYDRODEOXYGENATION; VALORIZATION; PYROLYSIS; MECHANISM; BIOMASS